COCONUT HUSK CHAR BIOSORPTIVITY IN HEAVY METAL DIMINUTION FROM CONTAMINATED SURFACE WATER - AJAYI-BANJI ADEMOLA; SANGODOYIN ABIMBOLA; IJAOLA OPOLOLA (Journal of Engineering Studies and Research)
Applicability of coconut husk char in heavy metal removal was examined in the study. The surface morphology and elemental compositions of the char was investigated with SEM-EDX machine. Heavy metals sorption on 100 g of the char dosage was studied under five different contact times in the column experiment. Isotherm and kinetic models were the probing tools for biosorption mechanism prediction. Results indicated removal efficiency for chromium, cobalt, cadmium, aluminum and arsenic at 60 mins contact time were 72, 80, 86, 89 and 100 % respectively. Contaminate removal depends on metal involved and sorption contact time. Adsorption data are fitted well into Freundlich isotherm model (R2 > 0.92). Pseudo kinetic second order well described the adsorption process, with most R2 values ≥ 0.94. Coconut husk char is an effective biosorbent in sequestration of arsenic, cadmium, aluminum and cobalt in contaminated surface water.